The Effect of Rock Decompaction on the Interaction of Movement Zones in Underground Mining - Melo-Hurtado, F; Vivanco-Avaria, F (2013)
An increased interest in scientific applications for underground mining, mainly to extend the productive life of open pit mines such as Chuquicamata in Chile, has motivated a growing effort to model experimental and theoretically phenomena found in these mines as well as the processes involved in their operation. There is a general consensus that contamination as a result of dilution, a critical problem found in the operation of underground mines, might be reduced by an adequate design of draw point grids and the appropriate handling of them. This requires understanding of the flow of rock fragments and the evolution of the movement zone created by the interaction of multiple draw points. In this paper, we present a theoretical study focused on determining the movement zone created by the interaction of two neighboring draw points operating in alternate mode that simulate those found in a sub-level caving mine. We employ a modified 2D kinematic model that includes a dilation front and assumes that rocks are restricted to move only along streamlines so that we may determine the modification of an isolated movement zone that results from the extraction of material from a neighboring draw point. The volume of extracted material required to initiate the interaction and the location where it occurs are predicted in terms of the material s previously extracted volume, diffusion coefficient, density variations, and extraction rate. The results show that the top surface of the previously isolated movement zone is modified in order to permit the surface to reach greater heights and displace its maximum position closer to the operating draw point. We also find that the regions outside of the operating draw point s isolated movement zone are affected by the interaction and this is confirmed by the deflection of tracer lines. This could have significant negative effects in underground mining operations because dilution, initially located out of range of an operating draw point, might be carried to either the neighboring draw points or the operating draw point s opening, consequently increasing pollution. The results presented can be extrapolated to 3D systems and generalized to other type of flows described by more complex models than a kinematic model. © 2013.